Is the Implementation of the Independent Curriculum Based on the Case Method Effective in Science Learning? - Syahfitriani Br Ginting; Sri Hanipah (Universitas Pendidikan Ganesha, 2025)
The implementation of the Independent Curriculum based on the case method in the current learning process has not yet been optimally carried out. This is due to the lack of understanding related to the application of the Independent Curriculum, particularly in IPAS (Integrated Science) learning. The purpose of this study is to analyze the implementation of the Merdeka Curriculum using the case method in IPAS learning at Elementary Schoo Wasur 2. The research method used is descriptive quantitative, with data collection through interviews, classroom observations, distribution of questionnaires involving the principal and 14 teachers from Elementary Schoo Wasur 2, as well as documentation, and the analysis of teaching modules. The results of the study show that the implementation of the Independent Curriculum based on the case method in IPAS learning faces many challenges and obstacles in the learning process, such as the lack of supporting facilities and infrastructure, and the available teaching materials are not yet sufficient to support IPAS learning. Inadequate knowledge and expertise of teachers in applying the case method. The purpose of this study was to examine how Wasur 2 Elementary School implemented an independent science curriculum based on the case approach.